Neuroprotective role of Celastrus paniculatus Willd and Sida cordifolia Linn on kainic acid-induced neuronal damage in neurodegenerative diseases - Gajanand R Pujari; Vijayalakshmi Subramanian; Suresh Rangogi Rao (Faculty of Pharmacy, Mahidol University, 2022)
Neurodegenerative diseases (NDs) are caused by the dysfunction of neurons. Neuronal death is associated with the aggregation of proteins in neurons and glial cells. The aggregated proteins impede mitochondrial function and induce oxidative stress. Increased oxidative stress produces more reactive oxygen species (ROS) which is detrimental to cells in the brain causes neuronal degeneration. There are no treatments for NDs other than reducing disease progression. Hence, the treatment strategies, which reduce oxidative stress and neuronal damage are in demand. Celastrus paniculatus Willd (CP) and Sida cordifolia Linn (SC) have been extensively used in the indigenous therapeutic systems for treating various brain-related ailments. The present investigation was carried out to examine the biochemical and histological alterations of seed oil of CP (SOCP) and aqueous root extract of SC (ARESC) on the hippocampus of the brain in Kainic acid (KA)-induced NDs. The extracts of SOCP and ARESC were administered for 14 days and KA was administered by i.p. on the 14th day to all the groups except the vehicle control group. At the end of the study, the rat brain was removed, the hippocampus was separated, and the homogenate was prepared to estimate the antioxidant parameters (SOD, catalase, and LPO). LDH assay, dopamine (DA) level, α-synuclein immunohistochemistry, and ROS assays were conducted. The results revealed that the treatment with SOCP and ARESC increased the levels of antioxidant enzymes, reduced oxidative stress, decreased α-synuclein protein aggregation, and elevated the levels of DA neurotransmitters.